Markenpositionierung durch Archetypen: Eine konzeptionelle Analyse mithilfe eines archetypischen Positionierungsmodells - Thomas Kratzer; Hans-Michael Ferdinand; Irene Kramer; Jens U. Pätzmann (Markenbrand, 2018)
– This article examines the archetypal brand positioning in the deodorant industry for men in Germany. It is based on the hypotheses that brand positioning follows archetypal principles and that the brands address either very similar or very different archetypes. A new positioning model is developed that enables the traceable classification of brands to archetypes. With the help of a criteria catalogue, eight deodorant brands for men are analysed and then put in the archetypal positioning model. Hence it can be observed that in the deodorant industry for men, the address of profoundly different archetypes is being conducted with the aim of reaching a differentiation from the competition.
Keywords: 650